Pengaruh Pembiayaan Murabahah dan Pembiayaan Musyarakah Pada Masa Pandemi Covid-19 Terhadap Pendapatan Usaha Nasabah di PT. BPRS Bumi Rinjani Kepanjen cabang Probolinggo (Periode bulan Maret-Desember 2021) - Yayuk Indah Wahyuning Tyas; Agung Yatiningrum (Politeknik Ganesha Medan, 2023)
This research was conducted at PT. BPRS Bumi Rinjani Kepanjen branch Probolinggo with the aim of knowing the effect of murabahah financing and musharakah on customer operating income for the period March-December 2020. This study aims to determine the customer's income after perform financing in Islamic banking PT. BPRS Bumi Rinjani Kepanjen Probolinggo branch and to determine the effect of financing murabaha partially, simultaneously on customer income. Population. in this study were 97 customers, while the sample used in this study using the slovin formula with the number a sample of 50 customers. The data source used is primary data and secondary. The data analysis technique used is descriptive analysis quantitative data collection techniques used in research. This is using a questionnaire. As for testing data analysis using the classical assumption test (normality test), the determination test of R2 square, test hypothesis statistics (t test, f test, dominant test). The results showed the value of t arithmetic t table (8.667 1.677) (sig. 0.000 0.05). This means that the Murabaha variable has a partial effect on Customer Business Revenue. Value tcount t table (2.703 1.674) (sig. 0.002 0.05). This means that the Musyarakah variable has a partial effect on Customer's Business Income, and the calculated F value is greater than F table (67,920>3,20) . The sig value is 0.000 < 0.05, so that there is significant influence between Murabahah and Musyarakah variables on Customer's Business Income